Characteristic Fe and Cu Compounds in Particulate Matter from Subway Premises in Japan and their Potential Biological Effects - Takuma Okamoto; Ayumi Iwata; Hiroko Yamanaka; Kako Ogane; Tatsuhiro Mori; Akiko Honda; Hirohisa Takano; Tomoaki Okuda (Aerosol and Air Quality Research)
Abstract Suspended particulate matter (PM) in subway premises contain high concentrations of metal components and distinctive compounds owing to their unique emission processes. However, little is known regarding the detailed chemical states of airborne PM and their biological effects. Therefore, to demonstrate the unique chemical states of the PM collected from subway premises and outdoors, this study compared the chemical speciation of iron (Fe) and copper (Cu) components using X-ray absorption fine structure analysis. The potential biological effects of these chemical states on humans were also investigated in vitro by assessing cell damage and its pathways in cells after exposure to several compounds. Compared with a reference outdoor PM sample, Fe was enhanced by at least 10 times in subway PM and the concentrations of several metal components, including Cu, contained in railway bodies, rail, overhead wires, and tunnel walls, also increased. In these chemical speciations, the compounds derived from wear processes with relatively high-temperature oxidation (Fe3O4, γ-Fe2O3, and monovalent Cu compounds) were detected among the Fe and Cu components in subway PM. Our cell-based bioassay suggested that the contribution of the Fe component to cell damage can be enhanced by the predominance of Fe3O4 in subway PM. In contrast to typical bivalent Cu compounds in the atmosphere, monovalent Cu compounds, which are characteristically identified in subway PM, exacerbate cell damage via different cell death pathways. Our results indicate that the chemical states of the distinctive compounds in the PM of subway premises differ from those in the typical atmosphere, thus exerting different biological effects. These findings suggest that the detailed chemical speciation is an important factor in accurately understanding their PM toxicities.